2008
DOI: 10.1089/hum.2007.161
|View full text |Cite
|
Sign up to set email alerts
|

Stable Integration of Recombinant Adeno-Associated Virus Vector Genomes After Transduction of Murine Hematopoietic Stem Cells

Abstract: We previously reported that among single-stranded adeno-associated virus (ssAAV) vectors, serotypes 1 through 5, ssAAV1 is the most efficient in transducing murine hematopoietic stem cells (HSCs), but viral second-strand DNA synthesis remains a rate-limiting step. Subsequently, using double-stranded, self-complementary AAV (scAAV) vectors, serotypes 7 through 10, we observed that scAAV7 vectors also transduce murine HSCs efficiently. In the present study, we used scAAV1 and scAAV7 shuttle vectors to transduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…60 Importantly, integration sites in the mouse genome have not been found within coding regions of known genes, including oncogenes, and infection in mice or humans with AAV has not been linked to any pathological abnormalities. 36,37 Our data indicate that AAV-mediated expression of GLP-1 in beta-cells following single intraperitoneal administration can mitigate the onset of diabetes in a model of type-1 diabetes. Targeted production of GLP-1 in beta-cells on its own, or coupled with a therapy designed to reduce autoimmune destruction, such as beta-cell expression of interleukin-4 as described by Rehman et al, 29 may represent a novel therapeutic strategy for type-1 diabetes.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 79%
See 2 more Smart Citations
“…60 Importantly, integration sites in the mouse genome have not been found within coding regions of known genes, including oncogenes, and infection in mice or humans with AAV has not been linked to any pathological abnormalities. 36,37 Our data indicate that AAV-mediated expression of GLP-1 in beta-cells following single intraperitoneal administration can mitigate the onset of diabetes in a model of type-1 diabetes. Targeted production of GLP-1 in beta-cells on its own, or coupled with a therapy designed to reduce autoimmune destruction, such as beta-cell expression of interleukin-4 as described by Rehman et al, 29 may represent a novel therapeutic strategy for type-1 diabetes.…”
Section: Aav-mediated Expression Of Glp-1 In Beta-cells Mj Riedel Et Almentioning
confidence: 79%
“…AAV vectors represent an innovative gene therapy tool, having reduced immunogenicity compared with that of adenoviruses, 36 while being capable of directing long-term expression of transgenes both in humans and in mice. 37-39 AAV8 appears not to be neutralized by antisera directed against other AAV serotypes, and only low levels of neutralizing antibodies against AAV8 have been detected in normal human subjects, 26,40 suggesting that immune responses that have been observed following AAV2-mediated gene therapy 41 may be minimized following AAV8 administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously demonstrated integration of AAV vector sequences in CD34 + cells by fluorescent in situ hybridization, Southern blots, and sequence analysis. 25,[35][36][37] Deep sequencing studies are in progress to further evaluate the status of the long-term surviving AAV vector genomes.…”
Section: Discussionmentioning
confidence: 99%
“…þ HSCs (Fisher-Adams et al, 1996;Chatterjee et al, 1999;Santat et al, 2005;Han et al, 2008) and efficient transduction of primitive, pluripotent, self-renewing human HSCs capable of supporting primary and secondary multilineage engraftment in immune-deficient nonobese diabetic/severe combined immunodeficiency mice (Santat et al, 2005). Subsequently, we showed that transduction of primitive HSCs capable of supporting serial engraftment was attributable to the propensity of rAAV to efficiently transduce primitive, quiescent CD34 þ CD38 -cells residing in G 0 (Paz et al, 2007).…”
mentioning
confidence: 99%